Improving Social Skills Using Pop-Up Media for Elementary School Students - Amir Pada; Faizal Amir (STAI Hubbulwathan Duri, 2023)
Students' social skills can be honed with various teaching techniques, including using learning media. The use of pop-up media is an option to help students develop social skills that are responsive to environmental issues. Thus, this study aims to analyze social skills using pop-up media in elementary schools. This study used a nonequivalent control group design and a quasi-experimental approach, treating the experimental and control groups differently. All 48 participants in this study were fourth graders, constituting the study population. The sample of this research is 48 people and based on the saturated sample technique. The data collection technique for this study used a closed questionnaire and observation. Descriptive and inferential data analysis methods include homogeneity, normality, and hypothesis analysis. Analysis of descriptive data on the influence of pop-up media on children's social skills development in social studies learning determined that the value of P = 0.005 is more diminutive than = 0.05. So, using pop-up media impacts how students build their social skills. Therefore, pop-up media can improve students' social skills in elementary schools, especially in responding to environmental issues and can be used as an alternative teaching technique for developing students' social skills.